Identification of Genes and Pathways Involved in Retinal Neovascularization by Microarray Analysis of Two Animal Models of Retinal Angiogenesis - Franco M. Recchia; Lili Xu; John S. Penn; Braden Boone; Phillip J. Dexheimer (2010)
Comparative retinal gene expression analysis in two rodent models of oxygen-induced retinopathy (OIR) was performed to identify the genes and pathways involved in retinal neovascularization.Three independent experimental runs were conducted for each species, according to standard protocols for induction of OIR. Total retinal RNA was isolated at two time points, corresponding to the early response to relative hypoxia (P13 in mouse, P15 in rat) and to the later phase of maximum retinal neovascularization (P18 in mouse, P20 in rat) and was used to prepare labeled probes for hybridization. Gene expression was compared between normal and experimental conditions for each species at each time point. Probesets with a false-discovery rate of <or=0.05 were considered significantly different and were classified as cellular functions or biological pathways. Changes in expression of selected genes were confirmed by quantitative rtPCR.At the early time point, there were changes in 43 genes in each species, with two in common. Increased expression of members of the VEGF and ephrin receptor signaling pathways were identified in both models. At the later time point, there were changes in 26 genes in the rat and in 1622 in the mouse, with 13 in common. Four pathways were identified in both models.Genes and pathways known to be involved in angiogenesis, as well as other biologically plausible genes and pathways, were identified. This work serves as a comprehensive resource for the study of retinal neovascularization and identification of potential rational targets for antiangiogenic therapy.